Past social support influences pre-performance self-confidence and performance quality among student musicians - Yoshie, Michiko; Morijiri, Yuki (Frontiers in Psychology, 2025)
Music performance anxiety (MPA) is a serious and prevalent problem among student musicians. Although previous studies have indicated the importance of social support from parents and teachers in the management of MPA, it remains unknown whether past social support influences pre-performance mental states and performance quality among student musicians. To address this, we asked 56 university-level music students to complete social support scales by recalling the social support they had received from their parents and a past music teacher before university enrollment, in addition to the social support they were receiving from a current music teacher. The students also recalled their most important public performance in the past six months, and they completed the Revised Competitive State Anxiety Inventory-2 and a performance evaluation scale. The results showed that social support from the past teacher positively predicted pre-performance self-confidence and performance quality. By contrast, social support from the current teacher positively predicted only performance quality and not pre-performance self-confidence. These findings highlight the differential roles of music teachers at different developmental stages of student musicians. Social support received from teachers by middle adolescence may be crucial for enhancing pre-performance self-confidence among student musicians.